Patient-Reported Outcomes among people living with Chronic Pruritus (PROs-CP): Protocol for a single-center, multistage, mixed-methods prospective cohort study in Thailand - Surapon Nochaiwong; Chidchanok Ruengorn; Salin Kiratikanon; Rujira Rujiwetpongstorn; Panjit Chieosilapatham; Napatra Tovanabutra; Siri Chiewchanvit; Ratanaporn Awiphan; Chabaphai Phosuya; Yongyuth Ruanta; Kednapa Thavorn; Mati Chuamanochan (PLoS ONE, 2025)
Background Although there have been well-validated patient-reported outcome (PRO) measurements in dermatology practice, there is limited evidence of the adopted comprehensive aspects of PRO measures in long-term follow-up among people living with chronic pruritus. As such, we aim to create a cohort study of the Patient-Reported Outcomes among people living with Chronic Pruritus (PROs-CP) in Thailand. Methods and design This study is a single-center, prospective, open cohort, observational longitudinal study using a multistage, mixed-methods parallel designs to integrate both quantitative and qualitative data regarding PROs among people living with chronic pruritus (itch lasting six or more weeks). The multistage of the PROs-CP study will comprise three sub-studies: (i) study I, PROs measure development, translation, and psychometric validation; (ii) study II, perspectives of people living with chronic pruritus to gain more information regarding disease burden and unmet treatment care responses; and (iii) study III, a longitudinal study to assess the impact of chronic pruritus on long-term health outcomes. Based on a comprehensive review of a panel of stakeholders with chronic skin disease, a set of PRO measurement tools will comprise an established validated Thai version. Meanwhile, meaningful non-Thai versions or unestablished PRO instruments will be translated and developed through this study as appropriate. Quantitative data will be collected based on PRO measures regarding pruritus symptoms and severity, disease activity control and treatment satisfaction, general- and dermatology-specific health-related quality of life, mental health and psychosocial issues, and psychosomatic symptoms. Qualitative data will be obtained from the patient’s perspectives through individual interviews. Ethics and dissemination The study protocol was approved by the Ethics Committee of the Faculty of Medicine, Chiang Mai University (MED-2566-0299), Thailand. Our findings will be disseminated through scientific conferences and publications in peer-reviewed journals. Conclusion Regarding the mixed-methods approach, this open cohort, prospective longitudinal study will provide an evidence-based better understanding of patient perspectives on chronic pruritus burden and inform the utility of a comprehensive set of PROs to measure their long-term health outcomes. Trial registration Thai Clinical Trials Registry (TCTR, thaiclinicaltrials.org) registration TCTR20240327001 (registered on March 27, 2024).